Association of Hypertension and Lipid Profile with Osteoporosis. (13th July 2020) - Al-Hariri, Mohammed; Aldhafery, Bander
Abstract : Background . Hypertension (HTN) and osteoporosis (OP) are common diseases that adversely affect the health-related quality of life among the elderly. However, there is a scarcity of literature on the association between HTN and OP. Objective . The aims of this study were to investigate the association between HTN and antihypertensive drugs (AHT), with bone mineral density (BMD) T -scores, as well as to determine the status of bone quality in Saudi Arabia. Method . A retrospective study was conducted at King Fahd Hospital of the University, Khobar, Saudi Arabia, during 2016 to 2018. BMD was measured using dual-energy X-ray absorptiometry (DEXA). T -score values were used for the diagnosis of osteoporosis. HTN diagnosis and medications, laboratory, and radiology results were collected from the hospital record system. Results . Out of 1332 extracted profiles, 1103 (82.8%) were females. Based on the T -score, the majority of patients either had osteopenia (41.1%) or was osteoporotic (27.8%). The present study found that there is a significant increase in serum lipids and alkaline phosphatase (ALP) in the osteoporotic group when compared with normal and osteopenia groups. Furthermore, it was found that ALP and Ca levels were significant predictors for OP. Pearson's correlation test revealed a significant negative correlation between HTN and BMD T -score. However, the study reported a nonsignificant association between AHT and BMD T -score. Conclusion . We conclude that controlling both HTN and dyslipidemia might improve bone health. Every osteoporotic patient should be screened for dyslipidemia. Early detection and appropriate management for OP are highly recommended in Saudi Arabia, especially amongst the high-risk group.